The Apostolic Fathers: revised texts with short introductions and English translations - Lightfoot, Joseph Barber; Harmer, J. R. (Macmillan, 1898)
Epistles of Celment of Rome. -- Epistles of S. Ignatius. -- Epistle of S. Polycarp. -- Martydom of S. Polycarp. -- Didache; or teaching of the apostles. -- Epistle of Barnabas. -- Shepherd of Hermas. -- Epistle to Diognetus. -- Fragments of Papias. -- Reliques of the Elders preserved by Irenaeus